(3WH GdbdH GdYdjd HYhGdi GHf Ndjds - (3YHO GdbGOQ Hf Ndjd GdeOfj,J (B1187 (3g` s ((3chcHGf HGdjef s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd bQH GdESfGO Edi fHjg (B( (3U(B) (3CbQH bQHI , hhUd ef hUd Edjg Hg s
(3BNQgG (B:s
,(3gPG GdMOjK ajg Hjfi hHjf GdfHi (B( (3U(B) (3CMO YTQ QLdkG hddg GdMeO hGdefI hgPG eG ChQOfGg ef GdCMGOjK GdYhGdi hbO EbJUQfG Ydi GdCQHYjf ceG fHgfG ai GdChd hbO fLRJ HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdbGVi CMeO Hf eMeO RHGQI GdNGUI (B- (3HUfYGA s
Keywords: (3GdCOHs